Student teachers’ interactional language: Changes and improvements through guided self-reflection during the internship period - Chen, Suanrong; Liu, Huifang; Chen, Jie (Frontiers in Education, 2022)
The case study aimed to investigate the changes in student teachers’ (STs) interaction language during their internship at local schools. The student teacher’ interactive language was measured by using the analytical tool of iFLAS, and intervention and interview were conducted afterwards. The study found that the student teacher’s interactive language keeps changing: the ratio of teacher language is increasing, while the ratio of student language and silence are decreasing; teacher’s direct instruction gradually shifts to indirect instruction; the number of positive integration grids grows larger, while the number of defect grids is getting smaller; the teacher asks more valid questions and makes more positive comments. The overall change did not come naturally, but due to the mentor’s instruction, the ST’s self-reflection, and the researchers’ prompt feedback of the iFIAS after each lesson. The study quantified the ST’s classroom language using iFIAS to provide a visualized understanding of the language. The findings can provide a reference value for future research on the interactive language of student teachers.